THE COMMUNICATIVE TURN IN GERMAN SOCIOLOGY OF KNOWLEDGE - KNOBLAUCH, HUBERT (Society Register, 2019)
In this paper, I want to start with a short sketch on the development of the German sociology of knowledge which has been quite successful in the last decade. Thus success is very much due to its orientation to the “Social Construction of Reality”. Its reception led first to research on language and then to a turn from language to communication which led into what came to be called communicative constructivism. This turn took very much an empirical form, so that we shall sketch the programme implicit in the empirical movement leading to communicative constructivism. Before we address the general sociological background for this movement, i.e. communication society and refiguration, we shall outline its major theoretical features which distinguish communicative constructivism from its predecessor, social constructivism.